EVALUATION OF JAVANESE GAMELAN CONCERT HALL ACOUSTIC DESIGN BASED ON PSYCHOACOUSTIC TEST - ABDALA (NIM : 13311036); IVAN STEFANUS (NIM : 13311076), FARIS
This final project aims to find the preferred value of room acoustic parameters for javanese gamelan music using psychoacoustic test and to evaluate and improve a previously designed javanese gamelan concert hall based on the psychoacoustic test results. Psychoacoustic tests is done in two stage. The first test is carried out to find the preffered value of subsequent reverberation time after the early reflections ([Tsub]p) using headphone to present the stimuli whereas the second test is carried out to find the preferred value of listening level ([LL]p) and the preferred value of initial time delay gap ([ITDG]p) using sound field simulation as stimuli presentaion method. The first test provide 1,2 Ã‚Â– 1,4 s as [Tsub]p while the second test provide 69 - 79 dB as [LL]p and an inconclusive result for [ITDG]p. The three parameters stated combined with another parameter called interaural cross correlation (IACC) are used as the basis for evaluating and improving the concert hall design. The evaluation is focused on the geometry and the materials used. The improvement is carried out by altering the basic geometry of the hall, adding more detail, and replacing the materials used in the inner surface based on concert hall standards and optimum acoustic parameters. The final design has satisfied the standards with the value of 76 dB for LL, 37 ms for ITDG, 1,4 s for Tsub, and 0,5 for IACC at 1 kHz.